Computational Intelligence for fault detection in power distribution network using ANN (International Journal of Engineering and Computer Science, 2015)
Early detection and location of faults in networks has been a major challenge in power systems engineering as it results in loss of energy,revenue and damage to equipment and facilities.Transmission and distribution lines are vital links between generating units and consumers. They are exposed to atmosphere, hence chances of occurrence of fault in transmission line is very high, which has to be immediately taken care of in order to minimize damage caused by it. This paper focuses on detecting the faults on electric power distribution network using artificial neural networks.    Analysis on neural networks with varying number of hidden layers and neurons per hidden layer has been provided to validate the choice of the neural networks in each step. The developed neural network is capable of detecting single line to ground and double line to ground for all the three phases. Simulation is done using MATLAB Simulink to demonstrate that artificial neural network based method are efficient in detecting faults on distribution system and achieve satisfactory performances.